Fear and Greed in Tax Policy: A Qualitative Research Agenda - Christopher C. Fennell; Lee Anne Fennell (Washington University Journal of Law & Policy, 2003)
While there is a general consensus that most people dislike paying taxes, more empirical data is needed to determine how, and to what extent, tax aversion plays a role in taxpayer behavior. If tax aversion occurs at significant levels, it becomes important to isolate and explore the constitutive elements of that aversion. A better understanding of the causes and components of tax aversion could spur useful innovation in tax design. In this Essay, we survey and mine existing bodies of empirical work for the insights they might bring to bear on these questions, while constructing a qualitative research agenda that begins to fill the remaining gaps. To focus our inquiry, we concentrate primarily on the federal income tax.
Keywords: Taxation; Social science research; Income tax; Tax evasion